A highly sensitive, nested polymerase chain reaction based method using simple DNA extraction to detect malaria sporozoites in mosquitos - Vythilingam, I.; Nitiavathy, K.; Yi, P.; Bakotee, B.; Bugoro, Hugo; Balbir, Singh; Wirtz, R.A.; Palmer, Kevin (UPM, 2000)
Dried Anopheles farauti mosquitos caught in Solomon Islands in 1990 were examined for malaria sporozoites by ELISA and nested polymerase chain reaction (PCR). Only heads and thoraces were used. Plasmodium genus-specific nested PCR amplifications were carried out on all samples. Of the 402 pools of mosquitos that were processed, 30 were positive for malaria. Nest 1 products of positive samples were subjected to further PCR amplifications with species-specific primers for P. falciparum and P. vivax. Twenty pools were positive for P. vivax by PCR while only 7 were positive by ELISA. For P. falciparum 2 pools were positive by both ELISA and PCR, and one of these was a pool which was positive for P. vivax by PCR and ELISA. Thus the sensitivity of PCR for P. vivax was 100% while the specificity was 96.7%. For P. falciparum the sensitivity and specificity were 100%. The PCR technique is highly sensitive and can be used on dried mosquitos which makes it a valuable tool for determining sporozoite rates of mosquitos, even in remote areas.